2020
DOI: 10.1097/jom.0000000000001775
|View full text |Cite
|
Sign up to set email alerts
|

Firefighter's Acute Inflammatory Response to Wildfire Suppression

Abstract: Objectives: The purpose of this study was to determine the inflammatory response to a 12-hour wildfire suppression shift, in firefighters attending the “Black Saturday” natural disaster. Methods: Thirty-eight male volunteer firefighters provided venous blood samples before and after a 12-hour firefighting shift. Pre- to post-shift changes in pro-inflammatory (Interleukin [IL]-1β, IL-2, IL-6, IL-8, IL-12P70, granulocyte macrophage-colony stimulating fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…• Significant increase in IL-6 and IL-8 and significant decrease in IL-10 after 12 h of fire suppression [ 97 ]…”
Section: Resultsmentioning
confidence: 99%
“…• Significant increase in IL-6 and IL-8 and significant decrease in IL-10 after 12 h of fire suppression [ 97 ]…”
Section: Resultsmentioning
confidence: 99%
“…Disaster Medicine and Public Health Preparedness smoke, ash, disturbed soil, and other chemical emissions from burning or smoldering structures, vehicles, and brush may also have contributed to respiratory irritation among these first responders. [17][18][19][20][21][22][23][24] Given the high proportion of responders reporting acute and ongoing post-response health symptoms and the potential for toxic exposures, responders should be encouraged to seek post-response medical care or evaluation. Barriers to seeking care should be identified and addressed to promote post-response health care.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the present study showing an increase in obstructive pathology based on spirometry results suggests a model of increased acute inflammation and activation of the innate immune system from wildfire smoke that results in tissue remodeling and decreased lung function ( Figure 6). firefighters and in vitro studies reported increased IL-6, a contributor to inflammatory lung pathology [33,34], in response to wildfire or wildfire smoke extract, respectively [35,36]. The firefighters were assessed in the acute phase and found increased serum levels of IL-6, IL-8 and decreased IL-10, while the lung epithelial cultures presented with increased IL-6 production in addition to other markers of COPD including dysfunction of tight junctions.…”
Section: Discussionmentioning
confidence: 99%
“…The ILC2 are important sources of IL-13 [ 32 ] and have been linked to asthma, an obstructive lung pathology. Additionally, studies in both firefighters and in vitro studies reported increased IL-6, a contributor to inflammatory lung pathology [ 33 , 34 ], in response to wildfire or wildfire smoke extract, respectively [ 35 , 36 ]. The firefighters were assessed in the acute phase and found increased serum levels of IL-6, IL-8 and decreased IL-10, while the lung epithelial cultures presented with increased IL-6 production in addition to other markers of COPD including dysfunction of tight junctions.…”
Section: Discussionmentioning
confidence: 99%